Substitution of gp120 C4 region compensates for V3 loss-of-fitness mutations in HIV-1 CRF01_AE co-receptor switching. Issue 1 (31st December 2023) - Yu, Yueyang; Feng, Yi; Zhou, Zehua; Li, Kang; Hu, Xiaoyan; Liao, Lingjie; Xing, Hui; Shao, Yimig
ABSTRACT: HIV-1 infection is mediated by a viral envelope subsequently binding to CD4 receptor and two main coreceptors, CCR5 (R5) for primary infection and CXCR4 (X4) in chronic infection. Switching from R5 to X4 tropism in HIV-1 infection is associated with increased viral pathogenesis and disease progression. The coreceptor switching is mainly due to variations in the V3 loop, while the mechanism needs to be further elucidated. We systematically studied the determinant for HIV-1 coreceptor switching by substitution of the genes from one R5 and one X4 pseudoviruses. The study results in successfully constructing two panels of chimeric viruses of R5 to X4 forward and X4 to R5 reverse switching. The determinants for tropism switching are the combined substitution of the V3 loop and C4 region of the HIV-1 envelope. The possible mechanism of the tropism switching includes two components, the V3 loop to enable the viral envelope binding to the newly switched coreceptor and the C4 region, to compensate for the loss of fitness caused by deleterious V3 loop mutations to maintain the overall viral viability. The combined C4 and V3 substitution showed at least an eightfold increase in replication activity compared with the pseudovirus with only V3 loop substitution. The site-directed mutations of N425R and S440-I442 with charged amino acids could especially increase viral activity. This study could facilitate HIV-1 phenotype surveillance and select right entry inhibitor, CCR5 or CXCR4 antagonists, for antiviral therapy.